Metabolic Risk Factors and Their Impact on Quality of Life in Patients with Pancreatic Cancer, Acute or Exacerbated Chronic Pancreatitis - I. N. Grigor’eva; O. V. Efimova; N. L. Tov; T. S. Suvorova; D. L. Nepomnyashchikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to evaluate metabolic risk factors and their impact on quality of life in patients with pancreatic cancer (PC) and in patients with acute or exacerbated chronic pancreatitis.Materials and methods. Forty-five patients with PC (group 1) and 141 patients with acute pancreatitis or exacerbated chronic pancreatitis (group 2) in an observational multicenter clinical cross-sectional uncontrolled study were examined. Clinical, laboratory and instrumental examination of patients and assessment of risk factors (lipid profile, blood plasma glucose, obesity, arterial hypertension) were carried out in accordance with clinical recommendations. Patients completed the SF-36 questionnaire once to assess quality of life at hospital admission before treatment.Results. In group 1, indicators of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) in blood serum (3.7 ± 0.2; 2.2 ± 0.2 and 0.8 ± 0.1 mmol/L) were lower than in group 2 (5.1 ± 0.1; 3.1 ± 0.1 and 1.2 ± 0.1 mmol/L; p < 0.05). Arterial hypertension was more common in group 1 (55.6 %) than in group 2 (34.8 %; p = 0.013). The presence of arterial hypertension increases the chance of having PC by 2.7 times (p < 0.05). Body mass index parameters, including obesity, as well as parameters of triglycerides, and fasting plasma glucose, did not differ between the groups. Logistic regression analysis revealed a direct relationship with PC HDL hypocholesterolemia (Exp B = 4.976; p < 0.001) and arterial hypertension (Exp B = 2.742; p = 0.027) and an inverse relationship — with hypercholesterolemia (Exp B = 0.204; p = 0.002). The chance of having PC was not associated with age, fasting plasma glucose ³ 7.0 mmol/L, obesity. Quality of life indicators were higher in group 1 than in group 2 on four SF-36 scales: bodily pain (68.1 ± 5.1 and 36.8 ± 2.0; p < 0.001), general health (51.1 ± 2.5 and 38.0 ± 1.7 points; p < 0.001), social functioning (74.7 ± 3.0 and 64.5 ± 2.2 points; p = 0.007), role emotional functioning (28.2 ± 5.2 and 12.5 ± 3.1 points; p = 0.007) and in the general domain “physical component of health” (40.2 ± 1.0 and 33.6 ± 0.8 points; p < 0.001). In group 1 with HDL hypocholesterolemia compared with its absence, the indicators of role emotional functioning (22.2 ± 5.1 and 51.9 ± 13.7 points; p = 0.020) were lower, with arterial hypertension compared with its absence — role physical functioning (5.0 ± 4.0 and 25.5 ± 7.5 points; p = 0.036) and role emotional functioning (16.0 ± 5.1 and 43.3 ± 8.8 points; p = 0.007) were lower.Conclusions. In patients with PC arterial hypertension was more common and the levels of total cholesterol, LDL-C and HDL-C were lower than in patients with acute or exacerbated chronic pancreatitis. The chance of having PC is directly associated with HDL hypocholesterolemia, with arterial hypertension, inversely — with hypercholesterolemia, and is not associated with age, fasting plasma glucose ³ 7 mmol/L, or obesity. In patients with PC, quality of life indicators were higher on four SF-36 scales and on the general domain “physical component of health” than in the group with acute or exacerbated chronic pancreatitis. In patients with PC metabolic factors significantly worsened self-assessment of quality of life in terms of role functioning; in patients with acute or exacerbated chronic pancreatitis there was no such association.